2011
DOI: 10.1159/000333232
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Risk of Malignancy in Subcategories of ‘Atypia of Undetermined Significance’

Abstract: Objective: To determine if focal ‘nuclear atypia’ or ‘microfollicular architecture’ portends a higher risk of malignancy than other subcategories of atypia of undetermined significance (AUS) in thyroid fine-needle aspirations (FNAs). Study Design: The frequencies of The Bethesda System for Reporting Thyroid Cytopathology (TBSRTC) categories were calculated from 3,956 thyroid FNAs interpreted over a 26-month period at The Johns Hopkins Hospital after adoption of TBSRTC. TBSRTC criteria were applied strictly. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
155
3
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 149 publications
(177 citation statements)
references
References 64 publications
17
155
3
2
Order By: Relevance
“…As a consequence of the above-mentioned factors the risk of malignancy in FLUS nodules as assessed on the basis of postoperative histopathological examination ranges from 4% up to as much as 50% [12,[22][23][24][25][26][27][28][30][31][32][33][34][35][36][37][38][39][40][41], so it exceeds by several times the values suggested by NCI recommendations. Many authors indicate that the final malignancy results were observed several times more frequently in AUS than in FLUS [7][8][9][10][11][12][13][14]. In our material, in 1 of 3 cases of FLUS with features of nuclear atypia a papillary cancer was found in postoperative examination.…”
Section: Prace Oryginalnementioning
confidence: 42%
See 3 more Smart Citations
“…As a consequence of the above-mentioned factors the risk of malignancy in FLUS nodules as assessed on the basis of postoperative histopathological examination ranges from 4% up to as much as 50% [12,[22][23][24][25][26][27][28][30][31][32][33][34][35][36][37][38][39][40][41], so it exceeds by several times the values suggested by NCI recommendations. Many authors indicate that the final malignancy results were observed several times more frequently in AUS than in FLUS [7][8][9][10][11][12][13][14]. In our material, in 1 of 3 cases of FLUS with features of nuclear atypia a papillary cancer was found in postoperative examination.…”
Section: Prace Oryginalnementioning
confidence: 42%
“…A particularly controversial problem is the degree of nuclear atypia (polymorphism) that allows the categorisation of aspirate as FLUS and not SM. Some authors even distinguish the separate category for smears with abnormalities in cellular nuclei, such as the presence of occasional nuclear grooves, an abnormal chromatin pattern, or nuclear overlapping and crowding [7][8][9][10][11]22].…”
Section: Prace Oryginalnementioning
confidence: 99%
See 2 more Smart Citations
“…However, the published reports after the widespread use of BRSTC informed highly variable risk of malignancy ranging between 6 %-96,7% in this group (3)(4)(5)(6)(7)(8). The malignancy rate in AUS/FLUS category of our center was 45,8% and is placed centrally in previosly reported wide risk spectrum (3)(4)(5)(6)(7)(8).…”
Section: Discussionmentioning
confidence: 73%